2019
DOI: 10.1590/1980-549720190042
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of caries and need for dental extraction in a Kaingang adult Indigenous population

Abstract: Introduction: The epidemiological profile of dental caries for Indigenous Peoples is complex and heterogeneous. The oral health of the Kaingang people, third largest Indigenous population from Brazil, has not been investigated so far. Objective: The purpose of this study was to assess the prevalence and severity of dental caries, in addition to the associated factors of the need of dental extraction among Kaingang adult Indigenous. Methods: A cross-sectional oral health survey was conducted among Kaingang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
8
1
2
Order By: Relevance
“…Dental caries affects without distinction of social class, however, it affects more low-income people, our study showed a prevalence of 100%, being higher than that reported by Soares and others (91.6%) 25 and Aamodt and others (99%) 26 , in adult indigenous residents of Kaingang-Brazil and Chiapas-Mexico; respectively. In relation to the dental caries experience, our study found average scores lower than those reported in adult Guaraní indigenous settlers (DMTF = 13.9) 27 , Xavantes-Brasil (DMTF = 14.25) 28 and from the Park.…”
Section: Discussioncontrasting
confidence: 61%
“…Dental caries affects without distinction of social class, however, it affects more low-income people, our study showed a prevalence of 100%, being higher than that reported by Soares and others (91.6%) 25 and Aamodt and others (99%) 26 , in adult indigenous residents of Kaingang-Brazil and Chiapas-Mexico; respectively. In relation to the dental caries experience, our study found average scores lower than those reported in adult Guaraní indigenous settlers (DMTF = 13.9) 27 , Xavantes-Brasil (DMTF = 14.25) 28 and from the Park.…”
Section: Discussioncontrasting
confidence: 61%
“…Cross-sectional OHIP-14 information was obtained for Indigenous and non-Indigenous populations from Australia and Brazil. Data were drawn from 4 sources: 1) the Australian National Survey of Adult Oral Health (NSAOH), 2004–2006 ( n = 3,899) (Slade et al 2007); 2) a large convenience sample of Indigenous Australian adults living in a rural setting in South Australia ( n = 400) (Parker et al 2012); 3) an oral health survey conducted with Kaingang adults living in an Indigenous land settlement in the south of Brazil ( n = 108) (Soares, Aragão, et al 2019); and 4) a cross-sectional study involving incarcerated women in a correctional facility in the south of Brazil ( n = 305) (Soares, Mendonça, et al 2019). Sampling weights were not applied to estimate networks with NSAOH data.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported in the studies conducted among the tribal population, there was a higher number of decayed teeth, and the need for dental extraction among those population was high. The reason for the increased need for extraction could be because of their lack of dental visits which in turn aggravated the oral disease conditions (Arantes and Frazão, 2018;Soares et al, 2019) In the present study the mean DMFT score of the study population was 4.4 whereas, in the study conducted on Sugali Tribes in Telangana Region, the mean DMFT was 5.90 ± 2.28 (Vijayakumar et al, 2017). Also, in a cross-sectional study conducted among 35 to 44 yrs old adults in a tribal population (Soares et al, 2019).Higher DMFT scores were also reported in few other studies (Sampaio et al, 2010;Nascimento et al, 1986;Lalloo et al, 2015) which is a contrast to the results of the present study.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, Decayed component of the DMFT score was more when compared with missing and illed component. Whereas in a study it was observed that two-thirds of the DMFT score accounted for missing teeth (Soares et al, 2019)…”
Section: Discussionmentioning
confidence: 93%